2023
DOI: 10.1002/mp.16224
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time radial reconstruction with domain transform manifold learning for MRI‐guided radiotherapy

Abstract: Background: MRI-guidance techniques that dynamically adapt radiation beams to follow tumor motion in real time will lead to more accurate cancer treatments and reduced collateral healthy tissue damage. The gold-standard for reconstruction of undersampled MR data is compressed sensing (CS) which is computationally slow and limits the rate that images can be available for real-time adaptation. Purpose: Once trained, neural networks can be used to accurately reconstruct raw MRI data with minimal latency. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…In this work, phantom, volunteer brain, and patient lung images were acquired with standard Cartesian TSE sequences. Non‐Cartesian sequences (e.g., spiral and radial sampling) have recently shown promise for dynamic tumor tracking for radiotherapy 52,63,64 . However, eddy currents are a significant additional challenge for non‐Cartesian acquisitions, often deviating k‐space trajectories and causing significant image artifact 30,65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, phantom, volunteer brain, and patient lung images were acquired with standard Cartesian TSE sequences. Non‐Cartesian sequences (e.g., spiral and radial sampling) have recently shown promise for dynamic tumor tracking for radiotherapy 52,63,64 . However, eddy currents are a significant additional challenge for non‐Cartesian acquisitions, often deviating k‐space trajectories and causing significant image artifact 30,65 .…”
Section: Discussionmentioning
confidence: 99%
“…Non‐Cartesian sequences (e.g., spiral and radial sampling) have recently shown promise for dynamic tumor tracking for radiotherapy. 52 , 63 , 64 However, eddy currents are a significant additional challenge for non‐Cartesian acquisitions, often deviating k‐space trajectories and causing significant image artifact. 30 , 65 In the future, we will investigate the application of DCReconNet to non‐Cartesian reconstruction and distortion‐correction problems.…”
Section: Discussionmentioning
confidence: 99%
“…However, for most of these accelerated MRI acquisition techniques, the gain in acquisition time results in longer reconstruction times. Fortunately, machine learning approaches that transfer computational processing to offline training of a neural network 99–102 may overcome long reconstruction times of accelerated acquisitions. In the future, latency for treatment planning and image guidance could be further reduced through use of patient representations composited from models that extract various representative states and their probabilistic variations.…”
Section: Image Guidancementioning
confidence: 99%
“…Three-dimensional MRI with adequate spatial resolution in real-time is currently challenging (Bertholet et al 2019), which compromises target tracking efficiency and accuracy (Glitzner et al 2015, Bourque et al 2018. To overcome the challenges, several studies have reported advanced 3D MRI reconstruction, including radial trajectory k-space reconstruction (Zhu et al 2018, Goldman-Yassen et al 2022, Waddington et al 2023 and hybrid methodologies leveraging both k-space and image domains (Shen et al 2022). Although these efforts have reduced reconstruction times while preserving MRI quality, practical application is still limited due to the reconstruction time lasting several hundred milliseconds per patient.…”
Section: Introductionmentioning
confidence: 99%